Сучасні наукові здобутки Національного ботанічного саду ім. М.М. Гришка НАН України - Zaimenko, N.V.; Cherevchenko, T.M.; Gaponenko, M.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The data on creation and development of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine are presented. The basic scientific achievements of last years in the field of plants conservation, introduction, breeding, landscape construction, allelopathy, medical botany, bioindication and biotechnology are elucidated.